Exfoliative Cytology in the Oral Mucosa of Patients with Fanconi Anaemia: A Morphometric Approach - Machado, Maria Angela Naval; Chaiben, Cassiano Lima; Castro, Andrea Santos; Bonfim, Carmem Maria Sales Sales; de Lima, Antonio Adilson Soares; D’Agulham, Anna Clara Duszczak (Journal of Dentistry Indonesia, 2017)
Patients with Fanconi anaemia (FA) are prone to develop squamous cell carcinomas at an early age. Exfoliativecytology can be used to detect changes to the health of the oral mucosa. Objective: The aim of this study was to evaluate morphometrical and morphological changes using exfoliative cytology and to analyse and quantify the proliferative activity using silver nucleolar organiser regions (AgNOR) in epithelial cells of the tongue in FA patients, after haematopoietic stem cell transplantation (HSCT). Methods: Oral smears were collected from the tongues of 20 FA children and adolescents after haematopoietic stem cell transplantation (FA) and 20 healthy children (C) using exfoliative cytology. The smears were stained using the Papanicolaou technique and silver impregnation. The cells were morphologically analysed and the nuclear area (NA), the cytoplasmic area (CA), and the nucleusto-cytoplasm area ratio (NA/CA) were calculated. Results: Mean values for the FA and C groups were: NA (71.85 and 55.21μm²; p< 0.01); CA (2127.48 and 1441.61μm²; p< 0.01); NA/CA (0.03 and 0.04; p< 0.01), respectively. A significant increase in the NA and CA for the FA group (p< 0.01) was seen, and an alteration in the NA/CA ratio. No morphological differences were found between the groups. Class I smears were predominant in both groups. No differences were found between the groups for the mean values of AgNORs per nucleus. Conclusion: This study suggests that morphological changes occurred in the oral epithelium cells of children and adolescents with Fanconi anaemia when subjected to HSCT.